PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI SEKOLAH DASAR: A Systematic Literature Review dan Bibliometric Analisis - Safitri, Lili; Muis, Jumaini (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2024)
A learning model is a plan or pattern used in the learning process to improve the effectiveness and efficiency of learning. One of the innovative learning models is Problem Based Learning (PBL). Problem based learning uses real problems as a starting point to develop students' critical thinking and problem solving skills. The purpose of this study is to analyze the trend of research publications regarding the implementation of PBL in elementary schools and its impact on student learning outcomes. The research method used was PRISMA, with article searches from the Google Scholar database and Publish or Perish software. The research stages include identification, screening, eligibility assessment, and inclusion of relevant articles. The results showed that the implementation of PBL in elementary schools can improve student learning outcomes, especially in terms of critical thinking and problem solving skills. However, problem-based learning also faces challenges in its implementation, such as time constraints and teachers' habits that still rely on conventional learning methods. These results show that problem based learning has great potential to improve the quality of learning in primary schools, although it requires proper adjustment and support for its implementation.